Gender differences on the interacting effects of marital status and health insurance on long-term colon cancer survival in California, 1995–2014. (November 2016) - Campbell, D.; Gorey, K.M.; Luginaah, I.N.; Zou, G.; Hamm, C.; Holowaty, E.J.
Highlights: The main effects of age, gender, marital status, health insurance and poverty on cancer survival are well known. Interactions explain four-fold more variability than main effects in USA cancer survival. The more diverse a population the more important it is to study health risk interactions.